Essential Constituents of Truffle in Kurdistan Region - Pshtiwan Abdullah Yousif; Aveen Faidhalla Jalal; Kaeuis Aziz Faraj (Zanco Journal of Pure and Applied Sciences, 2020)
Essential constituents of truffle distributed in three different habitats of Kurdistan Region were investigated. Carbohydrates are the most abundant macronutrient ranged from 24.5% to 37%, the protein content was 4.4-5.0 %, fat 2-2.5 %, ash 3-3.2 % and moisture 73-75 %. High level of Chitin, a water insoluble polysaccharide was determined, (21-25 % of DM). The obtained results show high concentration of macro elements, potassium, Calcium, Magnesium and sodium, lower contents of essential elements iron, zinc, copper and chrome were found. Chemical constituents responsible for the antioxidant actions were examined as antioxidant activity (FRAP values), ascorbic acid, total phenolic, total flavonoids, β-carotene, tannin, lycopene and overall anthocyanins stated on a dry mass basis were (13-17 mmol Fe+2 equivalent/100g), (14-15.6 mg/100g), (14-20 mg/g DM), (6.19-8.41mg/100g), (1.55-2.16 mg/100g DM), (10.9-17.3 mg/g) (0.03-0.06mg/100g) and (10-15mg/100g DM) respectively. Total phenolics were the major antioxidant compounds as compared to β-carotene and ascorbic acid content.